PERANCANGAN SISTEM INFORMASI INVENTARIS BARANG BERBASIS WEB PADA DISPORA SUMUT - Muhamad Alda; Deva Rangga Sahendra (STMIK Catur Sakti Kendari, 2023)
The design of the goods inventory system is the best solution for the North Sumatra Youth and Sports Office, which starts in a manual process which causes many problems that arise from the manual inventory process, from loss of goods data to the loss of the goods themselves. The web-based inventory is an access that can be monitored by all stakeholders in the North Sumatra Youth and Sports Office. The inventory information system that was built can record transactions of incoming goods, outgoing goods, stock of goods, use of goods, replacement of goods, submission of goods, data collection of inventory room locations and reports so that they can find out and provide fast, precise and accurate information every day. In this study using the method of observation and literature study with the flow of identifying problems, determining research objectives, studying literature, analyzing problems. The usefulness of this research also has an impact on each person in charge of the inventory of the North Sumatra Youth and Sports Office, making it easier for the head of equipment. All processes and stages based on a web database will have a positive impact on the inventory process at the North Sumatra Youth and Sports Office.